PERAN KUALITAS AUDIT DALAM MEMODERASI PENGARUH KOMPETENSI AUDITOR DAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP PENCEGAHAN FRAUD STAR - Dony Oktariswan; Rina Yuliyanti (Prosiding Seminar Nasional Pakar, 2020)
The purpose of this study is to empirically prove the Role of Audit Quality in Moderating the Effects of Auditor Competence and Government Internal Control Systems on Fraud Star Prevention. The population in this study were all Inspectorate Civil Servants in Bogor Regency totaling 99 people. The research sample uses census / saturation techniques. Data analysis techniques in this study used Partial least square path modeling (PLS-SEM) analysis. The results of the study: auditor competence and SPIP have a positive effect on fraud star prevention, audit quality and SPIP strengthen the positive effect of auditor competence on fraud star prevention